Towards an Indigenism Without Indigenous people? Encounters and Disencounters between the Inter-American Indian Institute and International Organizations (UNESCO, OIT) - Cunin, Elisabeth (2021)
In the 1940s and 1950s, Latin American indigenism played a central role in the thinking of international agencies to elaborate policies for indigenous populations. Several authors —Luis Rodríguez-Piñero, Todd Shepard— have highlighted the influence of Mexico on ILO and UNESCO, particularly around the concept of ‹‹integration››. Without questioning such continuity, this article also insists on the discrepancies, reinterpretations, and misunderstandings between the Inter-American Indian Institute, ILO and UNESCO. By appropriating the proposals of the Inter-American Indian Institute, international agencies transform the two central figures of indigenism —the ‹‹indigenous›› and the ‹‹anthropologist››— into globalized actors, relocatable in other contexts —the ‹‹underdeveloped›› and the ‹‹expert››—. The question of the relationship between rights and difference, between development and discrimination, at the heart of indigenism, remains unresolved.